Ultrasensitivity in the Cofilin Signaling Module: A Mechanism for Tuning T Cell Responses - Ramirez-Munoz, Rocio; Castro-Sánchez, Patricia; Roda-Navarro, Pedro (Frontiers in Immunology, 2016)
Ultrasensitivity allows filtering weak activating signals and responding emphatically to small changes in stronger stimuli. In the presence of positive feedback loops, ultrasensitivity enables the existence of bistability, which convert graded stimuli into switch-like, sometimes irreversible, responses. In this perspective, we discuss mechanisms that can potentially generate a bistable response in the phosphorylation/dephosphorylation monocycle that regulates the activity of cofilin in dynamic actin networks. We pay particular attention to the phosphatase Slingshot-1 (SSH-1), which is involved in a reciprocal regulation and a positive feedback loop for cofilin activation. Based on these signaling properties and experimental evidences, we propose that bistability in the cofilin signaling module might be instrumental in T cell responses to antigenic stimulation. Initially, a switch-like response in the amount of active cofilin as a function of SSH-1 activation might assist in controlling the naïve T cell specificity and sensitivity. Secondly, high concentrations of active cofilin might endow antigen-experienced T cells with faster and more efficient responses. We discuss the cofilin function in the context of TCR triggering and spatial regulation of plasma membrane signaling molecules.